Whole Genome Sequencing of Australian Candida glabrata Isolates Reveals Genetic Diversity and Novel Sequence Types - Biswas, Chayanika; Marcelino, Vanessa R.; Van Hal, Sebastiaan; Halliday, Catriona; Martinez, Elena; Wang, Qinning; Kidd, Sarah; Kennedy, Karina; Marriott, Deborah; Morrissey, C. Orla; Arthur, Ian; Weeks, Kerry; et al. (Frontiers in Microbiology, 2018)
Candida glabrata is a pathogen with reduced susceptibility to azoles and echinocandins. Analysis by traditional MLST has recognised an increasing number of sequence types (STs), which vary with geography. Here we utilized whole genome sequencing (WGS) to study the genetic diversity of 51 Australian C. glabrata isolates and sought associations between STs over two time periods (2002-2004, 2010-2017), and with susceptibility to fluconazole by principal component analysis (PCA). Antifungal susceptibility was determined using Sensititre YeastOneTM Y010 and WGS performed on NextSeq 500 platform (Illumina) with in silico MLST STs inferred by WGS data. Single nucleotide polymorphisms (SNPs) in genes linked to echinocandin, azole and 5-fluorocytosine resistance were analyzed. Of 51 isolates, WGS identified 18 distinct STs including four novel STs (ST123, ST124, ST126, ST127). Four STs accounted for 49% of isolates (ST3, 15.7%; ST83, 13.7%; ST7, 9.8%; ST26, 9.8%). Split-tree network analysis resolved isolates to terminal branches; many of these comprised multiple isolates from disparate geographic settings but four branches contained Australian isolates only. ST3 isolates were common in Europe, USA and now Australia, whilst ST8 and ST19, relatively frequent in the USA, were rare/absent amongst our isolates. There was no association between ST distribution (genomic similarity) and the two time periods or with fluconazole susceptibility. WGS identified mutations in the FKS1 (S629P) and FKS2 (S663P) genes in three, and one, echinocandin-resistant isolate(s), respectively. Both mutations confer phenotypic drug resistance. Twenty-five percent (13/51) of isolates were fluconazole-resistant (MIC ≥64 µg/ml) of which 9 (18%) had non wild-type MICs to voriconazole and posaconazole. Multiple SNPs were present in genes linked to azole resistance such as CgPDR1 and CgCDR1, as well as MSH2; however, SNPs occurred in both azole-susceptible and azole-resistant isolates. Although no particular SNP in these genes was definitively associated with resistance, azole-resistant/non-wild type isolates had a propensity to harbor SNPs resulting in amino acid substitutions in Pdr1 beyond the first 250 amino acid positions. Our study shows the value of WGS for high-resolution sequence typing of C. glabrata, discovery of novel STs and potential to monitor trends in genetic diversity. WGS assessment for echinocandin resistance augments phenotypic susceptibility testing.